2019
DOI: 10.1021/acs.est.9b03697
|View full text |Cite
|
Sign up to set email alerts
|

Development of S-Fluxametamide for Bioactivity Improvement and Risk Reduction: Systemic Evaluation of the Novel Insecticide Fluxametamide at the Enantiomeric Level

Abstract: Increasing numbers of novel pesticides have been applied in agriculture. However, traditional evaluation of pesticides does not distinguish between their enantiomers, which may lead to inaccurate results. In this study, systematic research on the chiral insecticide fluxametamide was conducted at the enantiomeric level. The methods for enantioseparation and semipreparative separation of fluxametamide enantiomers were developed. The optical rotation and absolute configuration of two enantiomers were determined, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 42 publications
0
49
1
Order By: Relevance
“…Usually, the enantiomers have the same physical and chemical properties but often have different bioactivity, toxicity, and environmental behavior [8]. For instance, the bioactivity of (+)‐ S ‐fluxametamide was 52.1−304.4 times higher than (−)‐ R ‐fluxametamide and the toxicity was more than 30‐fold relative to R ‐(−)‐isomer [9]. However, no enantioselective dissipation of fluxametamide was observed in cabbage and soil under field conditions [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the enantiomers have the same physical and chemical properties but often have different bioactivity, toxicity, and environmental behavior [8]. For instance, the bioactivity of (+)‐ S ‐fluxametamide was 52.1−304.4 times higher than (−)‐ R ‐fluxametamide and the toxicity was more than 30‐fold relative to R ‐(−)‐isomer [9]. However, no enantioselective dissipation of fluxametamide was observed in cabbage and soil under field conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the bioactivity of (+)‐ S ‐fluxametamide was 52.1−304.4 times higher than (−)‐ R ‐fluxametamide and the toxicity was more than 30‐fold relative to R ‐(−)‐isomer [9]. However, no enantioselective dissipation of fluxametamide was observed in cabbage and soil under field conditions [9]. Similarly, difenoconazole contains two chiral centers and have four stereoisomers; stereoselective study indicated the (2 S ,4 S )‐difenoconazole showed the highest toxicity, lowest bioactivity, and least enrichment in tomato and cucumber [10].…”
Section: Introductionmentioning
confidence: 99%
“…The acute toxicity of fluxametamide enantiomers toward honey bees has been evaluated. Its S ‐( + ) ‐ isomer exhibited 52.1–304.4 and 2.5–3.7 times higher bioactivity than the R‐ (−) ‐ isomer and rac‐ fluxametamide, respectively 23 . The S‐ (+) ‐ isomer showed more than 30‐fold higher acute toxicity than the R‐ (−)‐isomer.…”
Section: Novel Mechanisms Of Actionmentioning
confidence: 96%
“…Its S-(+)-isomer exhibited 52.1-304.4 and 2.5-3.7 times higher bioactivity than the R-(−)-isomer and rac-fluxametamide, respectively. 23 The S-(+)-isomer showed more than 30-fold higher acute toxicity than the R-(−)-isomer. Molecular docking studies have been performed with GABA receptor to monitor the mechanism of stereoselective bioactivity.…”
Section: Arylisoxazolinesmentioning
confidence: 96%
See 1 more Smart Citation